2007
DOI: 10.2478/v10026-007-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sewage sludge composts and potato pulp on uptaking of macroelements by the grain and straw of the spring triticale

Abstract: Taking into consideration the acid pH soil, high content of potassium in relation to nitrogen and phosphorus and the insignificant quantity of heavy metals in the potato pulp and the slight alkaline pH soil as well, high amount of nitrogen and phosphorus in relation to potassium in the municipal sewage sludge, the experiment was carried out in order to define the effect of composts from these waste on uptaking macroelements by the grain and the straw of the Wanad variety spring triticale. The vegetative -pot e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
9
1
1
Order By: Relevance
“…Wolna-Maruwka and Pilarski [11] obtained results similar to those achieved by the authors. The contents of dry matter and pH obtained in the authors' own experiment were typical for a normal process of sewage sludge composting [23]. In conclusion, it needs to be said that the process of composting has a destructive impact on pathogenic microorganisms inhabiting in sewage sludge.…”
Section: Resultsmentioning
confidence: 54%
“…Wolna-Maruwka and Pilarski [11] obtained results similar to those achieved by the authors. The contents of dry matter and pH obtained in the authors' own experiment were typical for a normal process of sewage sludge composting [23]. In conclusion, it needs to be said that the process of composting has a destructive impact on pathogenic microorganisms inhabiting in sewage sludge.…”
Section: Resultsmentioning
confidence: 54%
“…2, composed of municipal sewage sludge (50%), iron (II) sulphate (VI) heptahydrate (30%), urea (10%) and potassium salt (10%), and next by the granular fertiliser No. 4 These data show that higher crop yields are obtained with a higher percentage of municipal sewage sludge (50%) in the composition of granular fertilisers. The obtained results fi nd their confi rmation in the studies by many authors who observed that municipal sewage sludge and composts produced with it affected an increase in the crop yields as well as improved their qualitative traits…”
Section: Resultsmentioning
confidence: 86%
“…The granular fertilisers containing CaSO 4 • 2H 2 O increased signifi cantly the P, Ca and S contents in the test plants when compared to those containing FeSO 4 • 7H 2 O.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations